2021
DOI: 10.3174/ajnr.a6959
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ASPECTS and Core Volume on CT Perfusion: Impact of Time since Stroke Onset and Presence of Large-Vessel Occlusion

Abstract: BACKGROUND AND PURPOSE: Both ASPECTS and core volume on CTP are used to estimate infarct volume in acute ischemic stroke. To evaluate the potential role of ASPECTS for acute endovascular treatment decisions, we studied the correlation between ASPECTS and CTP core, depending on the timing and the presence of large-vessel occlusion. MATERIALS AND METHODS:We retrospectively reviewed all MCA acute ischemic strokes with standardized reconstructions of CTP maps entered in the Acute STroke Registry and Analysis of La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 38 publications
3
35
1
Order By: Relevance
“…Details on the neuroimaging protocol of each participating center, ASPECTS scoring and adopted EVT guidelines have been published before, 12,13 and additional information are provided in the Supplementary Material.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Details on the neuroimaging protocol of each participating center, ASPECTS scoring and adopted EVT guidelines have been published before, 12,13 and additional information are provided in the Supplementary Material.…”
Section: Study Design and Study Populationmentioning
confidence: 99%
“…Prior studies, on the other hand, have shown improved performance of NCHCT-ASPECTS with increasing time after last known well. 20…”
Section: Discussionmentioning
confidence: 99%
“…Nannoni et al reported that NCCT ASPECTS correlated signi cantly with the CTP infarct core, especially in the AIS patients with late window and large-vessel occlusion. Therefore, they concluded that the use of ASPECTS could be a surrogate maker of CTP core in late-arriving AIS patients with large-vessel occlusion [14]. In addition, simulated multiphase CTA reconstructed from CTP raw data was also reported to be useful in re ecting the perfusion information to a certain extent.…”
Section: Discussionmentioning
confidence: 99%